Clinical and molecular characterization of Y microdeletions and X‐linked CNV67 implications in male fertility: a 20‐year experience. (29th July 2019) - Pinho, A.; Barros, A.; Fernandes, S.
Abstract: Background: Approximately 15% of couples worldwide are affected with infertility, attributed to a male co‐factor in about half of the cases. Y chromosome microdeletions are the second most common genetic cause for male infertility, with a global prevalence of 2–10% in infertile men. Recently, CNV67, localized in X chromosome, has emerged as potential contributor to male infertility, with a described frequency of 1.1% in the oligo/azoospermic men. Objectives: To investigate the prevalence of Y‐linked CNVs in a cohort of Portuguese infertile men and correlate the patients' phenotypes with a genetic alteration; to investigate the CNV67 deletion in a subset of patients and corroborate the role of this CNV in male infertility. Materials and methods: We retrospectively analysed a database of 4000 Portuguese infertile men for karyotype anomalies and Y microdeletions and selected a cohort of 400 for CNV67 screening analysis by quantitative PCR or single PCR plus/minus. Results: Karyotype anomalies were present in 263 patients (6.6%), with Klinefelter syndrome representing the most frequent karyotype anomaly (2.8%). Among the 4000 patients, the prevalence of Yq microdeletions was 4.6%. Ninety microdeletions (10.0%) were found in the azoospermic group, 44 deletions (4.5%) in the severe oligozoospermic group, 1 AZFc partial deletion (0.3%) in the mild–moderate oligozoospermic group and 2 partial AZFc deletions (0.4%) in the normozoospermic group. Complete AZFc deletions represented 56.8% of the Yq microdeletions. The CNV67 deletion frequency was 1.2% in the studied sample. Conclusions: This study presents one of the largest samples of infertile men worldwide with the main purpose of correlating the Yq microdeletions with sperm count. Our findings are supported by previous reviews with large data and provide a reliable estimation of the prevalence of these anomalies in a Portuguese population. CNV67 was exclusively deleted in patients with spermatogenic impairment, showing a consistent genotype–phenotype correlation and a significant prevalence.